Determinan Faktor Terjadinya Multidrug Resistant pada Pengobatan TB Paru (MDR-TB) di Rumah Sakit Umum Daerah dr. Zainoel Abidin - M. Rizal Fahlafi; Said Usman; Nizam Ismail (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Cases of multidrug resistant tuberculosis (MDR-TB) continue to increase. MDR-TB is the biggest problem in the prevention and eradication of TB, this is thought to have something to do with characteristics, environment, behavior and other disease factors. This study will examine the determinants of MDR-TB in RSUDZA Banda Aceh because it is a referral hospital for MDR-TB examination and treatment in Aceh Province. This type of research is analytic observational with case control design. The population is MDR-TB patients who seek treatment at RSUZA in 2018 as many as 37 people. By using a ratio of 1:1, the number of samples is 74 people consisting of 37 cases and 37 people as controls. Data collection was carried out from 20 to 30 August 2019 using questionnaires and observations. Data analysis used logistic regression test using the Stata program. The results showed that the variables that had significant values ​​were as follows: occupation with the occurrence of MDR-TB (P value = 0.036; OR = 5.6 95%CI: 1.12-28.1), smoking with the occurrence of MDR-TB (P value = 0.034; OR = 2.8, 95% CI: 95% CI: 1.07-7.52), side effects with the occurrence of MDR-TB (P value = 0.006; OR = 5.6, 95% CI: 1.64-1920) and history of diabetes with the occurrence of MDR-TB (P value = 0.001; OR = 4.9, 95% CI: 1.85-13.42). The results of the multivariate analysis obtained a history of DM (OR = 9; 95% CI: 2.53-37.47), (p = 0.0001) meaning that respondents who had a history of DM tended to be 9 times more at risk for MDR-TB compared to other variables. . The Aceh Health Office needs to improve the discovery of MDR-TB cases by conducting gene-expert examinations on TB patients suspected of having MDR-TB.